Plan de negocios para la creación de una empresa productora y comercializadora de ajo orgánico en la ciudad de Quito - Palacios Egas, Karla Katerine (2016)
The Project is focused on the production and commercialization of organic garlic, is called this way as the crop process is a hundred percent ecologic, garlic is an essential condiment in the kitchen, as well as many health benefits and is used in the industry. The zone that meet the requirements to execute the project is the parish of Pilahuín, at the Tungurahua province. The market study accomplished in the city of Quito, determined that the ninety per cent of the respondents population, is willing to consume organic garlic. The products that are going to be processed and commercialized are: garlic with shell, peeled, chopped and garlic paste, these products have had a good market acceptance, especially by Corporación La Favorita supermarkets. The project is objective is not only to obtain economic benefits for the investors, but getting social inclusion of the indigenous communities, by giving places of employment and being a source of income that improve the quality of life of their families, avoiding migration to bigger cities. The execution plan is to cultivate using new agricultural techniques to guarantee the quality and quantity of the product, likewise processing technology will be provided to meet the highest standards of quality and hygiene. Being a Green Company, conscious about the environmental care, ecological agricultural techniques are going to be used, this means the closest to the natural production, as the company is not going to use chemical substances that erode the soil, pollute the environment and are a health hazard of the people that consume crops cultivated in a traditional way.